Decision Support System Employee Performance Appraisal Method Using TOPSIS - Febrian, Tri Benny; Simangunsong, Agustina (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Employee performance is the level of achievement of an employee of a particular task that is influenced by internal and external factors of the company where the employee works. Employee performance is influenced by many factors including competency, attendance, loyalty and length of work. The purpose of this study is to create and design a Decision Support System (SPK) for evaluating employee performance using the TOPSIS method and applying the method to employee performance evaluation SPK. TOPSIS is a decision-making method that has multiple criteria or criteria. This type of research is a quantitative descriptive method that presents methods and research objects based on numbers. The study population was 42 employees at PT Catur Karya Sentosa and used as many as 4 employees as research samples and data were collected by interview method. The results showed that the calculation of employee performance using the TOPSIS algorithm runs well and efficiently and can be done every month so as to minimize or even eliminate the employee performance appraisal method subjectively. Ranking taken from the results of this method is the final result after the calculation of positive and negative ideal solutions as consideration of the final decision making by the board of directors.